SOME ASPECTS OF THE OPERATIONAL ACTIVITIES PROCEDURE’S OPTIMIZATION - Makans, Leonīds (Administrative and Criminal Justice, 2019)
The paper deals with the problem of the operational activities measures’ use in general and the specific method depending of the stage of the operational activities’ procedure. On the basis of the historical and theoretical foundations’ study of the operational activity on this issue, and on other countries’  experience, as well as the relevant legal acts, a conclusion was drawn on the disproportionate distribution of operational-activities’ measures on the  investigatory examination and investigatory process’s  stages. The proposals were made to amend the Operational Activities Law on this issue.